Konstruksi Keyakinan Hakim Mahkamah Konstitusi dalam Putusan Perselisihan Pemilukada - Mariyadi Faqih (Jurnal Konstitusi, 2016)
The fact is the basis of law for judges of the Constitutional Court in decisions. The fact is the law of another language of the evidence. The decision thus reflects the role of judges in unearthing, interpreting and discovering the laws (rechtsvinding) to resolve disputes elections of regional heads. The role of the judge is not out of conviction to assess the evidence. One of the tools of evidence that requires precision and accuracy in their assessments are witnesses, because witnesses can lie or correct the error and blamed the truth.